Are we delivering high-quality medical oncology care? A national comparison of severe acute toxicity from systemic anti-cancer therapy. (March 2023) - Boyle, Jemma M; Meulen, Jan van der; Kuryba, Angela; Cowling, Thomas E; Booth, Christopher; Fearnhead, Nicola S; Braun, Michael S; Walker, Kate; Aggarwal, Ajay
Abstract: Background: In the precision medicine era the complexity of systemic anti-cancer therapy (SACT) delivery and their associated toxicities have also increased. However, there has been little systematic assessment of the quality of care associated with systemic anti-cancer therapy delivery across national healthcare systems. We evaluated hospital-level severe acute toxicity rates during SACT treatment as a means of identifying variation in care quality. Methods: All colorectal cancer (CRC) patients receiving SACT within 106 English National Health Service (NHS) hospitals between 2016 and 2019 were included. Severe acute toxicity rates were derived from hospital administrative data using a validated coding framework. Toxicity rates were adjusted for age, sex, comorbidity, performance status, tumour site, and TNM staging. Variation in hospital-level toxicity rates was assessed separately in the adjuvant and first-line metastatic settings. Results: 8, 173 patients received SACT in the adjuvant setting, and 7, 683 patients in the first-line metastatic setting. Adjusted severe acute toxicity rates varied between hospitals from 11% to 49% for the adjuvant cohort, and from 25% to 67% for the metastatic cohort. Compared to the national mean toxicity rate in the adjuvant cohort, six hospitals were more than 2 standard deviations (2 SD) above, and four hospitals were more than 2 SD below. In the metastatic cohort, six hospitals were more than 2 SD above, and seven hospitals were more than 2 SD below the national mean toxicity rate. Overall, 12 hospitals (12%) had toxicity rates more than 2 SD above the national mean, and 11 (10%) had rates more than 2 SD below. Conclusion: There is substantial variation in hospital-level severe acute toxicity rates in both the adjuvant and metastatic settings, despite risk-adjustment. Ongoing national public reporting of this performance indicator can be used investigate reasons for variation in toxicity rates and stimulate quality improvement initiatives to improve care. This may include increasing centralisation of SACT care delivery to minimise variation. This approach can be applied across different cancer types and in many different countries where similar regional or national clinical and administrative hospital datasets are available.